THE RIGHT OR OBLIGATION OF THE EMPLOYER TO PROVIDE LEAVE - A COMPARATIVE LEGAL ANALYSIS IN FOREIGN EXPERIENCE - Xolmurodov, Xusan Doniyor o‘g‘li; Rahimqulova , L.U. (Educational Research in Universal Sciences, 2023)
This article discusses the issue of the right or obligation of the employer to provide annual leave and other leaves under the laws of foreign countries, with a comparative analysis of their experience.